Pendekatan Child-Friendly Spaces pada Perancangan Pusat Kreativitas Anak di Kota Banda Aceh - Ghina Salsabila (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2018)
The rapid growth of city construction and technological development in the city of Banda Aceh has a negative impact on children. Some problems arise such as reduced space for creativity and play for children, the emergence of children as gadget addicts, high child apathy towards the environment, low children's ability to solve problems and so on. This can hamper the potential and process of children's social interaction. The aspect of creativity is very important in overcoming these various problems. Presence of child-friendly creativity centre can accommodate and provide facilities for children. Child-friendly space focuses on providing recreational educational tools with an approach to children's interests and behavior. Embodiment of child-friendly space, namely by providing a space for creativity that is relaxed and nuanced by children, safe and comfortable, structured and flexible, can encourage self-expression, the existence of physical activity space, effective space for parents and teachers, and provision of furniture according to age groups child. This design aims to provide a representative spaces for children's creativity so as to realize a generation which is active, creative and innovative in the future.